HIROSHIMA AND NAGASAKI: 75TH ANNIVERSARY REFLECTIONS - Himes, Kenneth R. (Asian Horizons, 2020)
August of this year is the 75th Anniversary of the first and only use of atomic weapons in war, the bombings of Hiroshima and Nagasaki. The essay recounts the changes in the historical account of the bombings since then, and the evidence suggesting that the bombings were unnecessary to end the war. Using the revised history, there is a moral assessment of the decision to drop the bombs. Employing norms that are common to the just war tradition, the author argues that the decision to attack the Japanese cities was morally flawed. Based on the standards of innocents being immune from direct attack, the inappropriateness of a demand for unconditional surrender according to right intention, and the idea of proportionality in causing harm, there is a serious case against the justice of the atomic bombings. The essay concludes by noting evidence that many Americans continue to uphold military practices that violate basic ethical norms.